2018
DOI: 10.1111/irfi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Stock Liquidity and Firm Value: Evidence from a Policy Experiment in India

Abstract: The Indian securities market regulator intervened in June 2010 with a regulatory amendment in the listing requirement that mandated all the listed firms other than PSUs (government‐owned companies) to have a minimum public shareholding of 25%. The affected firms were given a 3‐year window to comply with the regulation. This study examines the impact of the new regulation on the affected firms’ value. We explore the relationship between improvement in firms’ value and stock liquidity. This regulatory interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…However, there was no causality between liquidity and the financial performance of the firms. Jawed and Kotha (2020) examined the relationship between improvement in firms' value and stock liquidity in India. Findings from the study confirmed the existence of a direct causality between stock liquidity and firm value, stemming from an improved operating performance.…”
Section: Causal Relationship Between Liquidity and Financial Performancementioning
confidence: 99%
“…However, there was no causality between liquidity and the financial performance of the firms. Jawed and Kotha (2020) examined the relationship between improvement in firms' value and stock liquidity in India. Findings from the study confirmed the existence of a direct causality between stock liquidity and firm value, stemming from an improved operating performance.…”
Section: Causal Relationship Between Liquidity and Financial Performancementioning
confidence: 99%
“…The outcomes depict a weak but positive association among the studied variables. More so, Jawed (2017), to determine the dynamic interaction among some concerned variables, examines the existing rules governing the pattern of shareholding ability in India. The study, which uses the ordinary least square method, discovers that a variation in the liquidity status of stocks of companies in India is directly related to the variation in the performance of such companies.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Extensive literature addresses a set of control variables in Q regressions to report the relationship between stock liquidity and firm value. Cheung et al (2015), Jawed and Kotha (2018), and many more estimate the influence of firm age, firm size, debt to asset, short-term debt, long-term debt, and other firm-specific variables on firm value. Cheung et al (2015) assert that firm size and age improve firm value by ensuring economies of scale or by minimizing information unevenness with established firms, whereas financial leverage can affect firm value both positively or negatively contingent on whether the rewards (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tobin's Q as a widely used measure of firm value allows researchers to investigate not only the past performance of the companies but also the future growth opportunities in it (Sauaia & Castro 2002). Scholars such as Brogaard et al (2017), Cheung et al (2015), Jawed and Kotha (2018), Raković (2018), Nguyen et al (2016), Tahir (2020), Morck et al (1988), Gompers et al (2003), etc. use Tobin's Q as a measure of firm performance in their study.…”
Section: Firm Valuementioning
confidence: 99%
See 1 more Smart Citation